Comparison of the effectiveness of quantiferon TB-gold in tube test with tuberculin skin test for the diagnosis of latent tuberculosis infection in immunosupressed patients - Deveci, Figen; Ilhan, Nevin; Turgut, Teyfik; Yildirim, Funda; Muz, Mehmet Hamdi (My University, 2012)
Objective: To compare the diagnostic value of the tuberculin skin test (TST) and the Quantiferon TB-Gold- In tube (QFT-GIT) test for diagnosis of latent tuberculosis (LTB) in immunosuppressive (IS) patients. Material and Method: 50 IS patients and 23 non-IS patients with LTB were included into the study. White blood cells, lymphocyte, albumin levels and QFT-GIT levels were measured.Results:TST was positive in 38 (74.5%) of IS patients. Mean QFT-GIT levels was statistically higher in non-IS patients with LTB (4.66±4.56 IU/mL)than IS patients with TST positive (0.92±1.50 lU/mL) (p=0.002). There was no significantly difference for the positive response rate of QFT-GIT between non-lS patients with LTB and all IS patients X2 =3.667, p=0.055). When evaluated only IS patients group, there was no significantly difference for the positive response rate of QFT-GIT between TST positive and negative subjects (X2=2.360, p=0.125). In addition, sensitivities of QFT-GIT was 47% and specificities was 77% for diagnosis of LTB in this group. Accordingly, the kappa (k) statistic for the agreement between the two tests was low (54.9%, K=0.170). When evaluated all subjects, there was a positive correlation between QFT-GIT and TST (r=0.453; p=0.000). Conclusion: We conclude that there was no notable difference between QFT-GIT test and TST particularly for our country.
Immunsüpresif hastalarda latent tüberküloz enfeksiyonu tanisinda tüberkülin deri testi ile quantiferon-tb git testinin etkinli?inin karşilaştirilmasi
Keywords: Immunosuppressive patients; Interferon-? release assay; Latent tuberculosis; Tuberculin skin test